A Review of the Therapeutic Potential of Recently Developed G Protein-Biased Kappa Agonists - Mores, Kendall L.; Cummins, Benjamin R.; Cassell, Robert J.; van Rijn, Richard M. (Frontiers in Pharmacology, 2019)
Between 2000 and 2005 several studies revealed that morphine is more potent and exhibits fewer side effects in beta-arrestin 2 knockout mice. These findings spurred efforts to develop opioids that signal primarily via G protein activation and do not, or only very weakly, recruit beta-arrestin. Development of such molecules targeting the mu opioid receptor initially outpaced those targeting the kappa, delta and nociceptin opioid receptors, with the G protein-biased mu opioid agonist oliceridine/TRV130 having completed phase III clinical trials with improved therapeutic window to treat moderate-to-severe acute pain. Recently however, there has been a sharp increase in the development of novel G protein-biased kappa agonists. It is hypothesized that G protein-biased kappa agonists can reduce pain and itch, but exhibit fewer side effects, such as anhedonia and psychosis, that have thus far limited the clinical development of unbiased kappa opioid agonists. Here we summarize recently discovered G protein-biased kappa agonists, comparing structures, degree of signal bias and preclinical effects. We specifically reviewed nalfurafine, 22-thiocyanatosalvinorin A (RB-64), mesyl-salvinorin B, 2-(4-(furan-2-ylmethyl)-5-((4-methyl-3-(trifluoromethyl)benzyl)thio)-4H-1,2,4-triazol-3-yl)pyridine (triazole 1.1), 3-(2-((cyclopropylmethyl)(phenethyl)amino)ethyl)phenol (HS666), N-n-butyl-N-phenylethyl-N-3-hydroxyphenylethyl-amine (compound 5/BPHA), 6-guanidinonaltrindole (6′GNTI), and collybolide. These agonists encompass a variety of chemical scaffolds and range in both their potency and efficacy in terms of G protein signaling and beta-arrestin recruitment. Thus unsurprisingly, the behavioral responses reported for these agonists are not uniform. Yet, it is our conclusion that the kappa opioid field will benefit tremendously from future studies that compare several biased agonists and correlate the degree of signaling bias to a particular pharmacological response.